Mutations in the “hot spots” of the FLT3, NPM1, IDH1, IDH2 and DNMT3A genes in acute myeloid leukemia - E. N. Voropaeva; M. V. Burundukova; A. A. Lyzlova; I. A. Chukhontseva; V. N. Maksimov; T. I. Pospelova (Сибирский онкологический журнал, 2025)
The purpose of the study was to systematize and present up-to-date data on the prevalence, combination and clinical significance of mutations in the “hot spots” of the FLT3, NPM1, IDH1, IDH2, DNMT3A genes in acute myeloid leukemia (AML). Material and methods. A search was conducted for available domestic and foreign literary sources published in the PubMed and RSCI database over the past 10 years. 509 sources were found. Publications such as “letters to the editor” and “comments” on published works, animal and cell model studies, as well as works on secondary AML, AML/myelodysplastic syndrome were excluded from the analysis. Mostly more recent works with the full text of the publication available in Russian or English were used. As a result, 66 papers were included in this article. The results of high-performance sequencing AML samples (1567 adults and 144 children) presented in the C-Bioportal for cancer genomics database (C-Bioportal) were analyzed. Results. In published scientific studies, there is a different spectrum of simultaneously investigated mutations, different methodological approaches and a small volume of studied samples of patients with AML. It was found that at the time of diagnosis of leukemia in patients, several driver mutations in the NPM1, IDH1/2, FLT3 and DNMT3A genes may be detected, which implies their molecular synergy contributing to tumor development. The available scientific data indicate the accumulation of recurrent mutations of the FLT3, NPM1, FLT3, IDH1 and IDH2 genes in leukemia, starting from the stage of clonal hematopoiesis of unknown significance and ending with the debut of AML or its recurrence. According to the results of the analysis of the C-Bioportal, at the time of diagnosis of the disease, 46.6 % of patients have isolated or combined prognostically significant mutations DNMT3A p.R882, NPM1 p.W288cfs*12, FLT3-ITD and FLT3-TKD, IDH1 p.R132, as well as IDH2 p.R140; 35 % – mutations for which targeted drugs have been developed (Flt3, idH1 and idH2 inhibitors); in every fifth (18.1 %) case of AML NPM1 p.W288cfs*12 can be detected, which is used as an independent target for the molecular assessment of minimal residual disease (MRD), and in a third of cases, targets for the assessment of MRD, which should be studied in combination with additional markers (FLT3-ITD and FLT3-TKD, IDH1 p.R132, IDH2 p.R140). Conclusion. Due to the fact that in real clinical practice, NGS remains an inaccessible method for patients to date, it is advisable to screen the population of patients with AML for the presence of clinically significant mutations in the “hot spots” of the recurrent mutating NPM1, IDH1/2, FLT3 and DNMT3A genes.